Transformation Of Administrative Service at Ballaparang Community Health Center Rappocini District Makassar City - Rahma Rahma; Mohammad Yunus; Henni Zainal (Public Resource Innovation Management and Excellence, 2026)
This study aims to determine the transformation that occurred at the Ballaparang Community Health Center, Rappocini District, Makassar City and the supporting and inhibiting factors in the implementation of the transformation carried out during the service at the Ballaparang Community Health Center. Transformation has occurred at the Ballaparang Community Health Center, the transformation was carried out in the administrative services section of the Community Health Center in the form of a transformation from manual services to technology-based services. The location of this research was carried out at the Ballaparang Community Health Center, Rappocini District, Makassar City, with the consideration that the Ballaparang Community Health Center has carried out a transformation of administrative services. The method used in this study is a qualitative method, meaning that this study is based on data taken from interviews with informants, field notes and documentation (official documents). Then it will be described or described according to the data obtained during interviews with informants. The results of this study are that the Ballaparang Community Health Center has carried out a transformation of administrative services in the form of using applications by utilizing computers or laptops to accommodate patient data who come to check their health, in addition the Community Health Center has also provided online registration for people who want to come to the Community Health Center. The community also felt satisfied with this latest service even though initially patients were still confused with the new system used by the Ballaparang Community Health Center.